Comparison of individual and paired drill practice methods on backhand drive accuracy table tennis game - Egi Ginanjar Saputra; Indra Safari; Adang Sudrazat (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This research is motivated by the lack of ability of high school students in making drive strokes, especially backhand strokes so that they are not on target. Therefore, the students have problems in the game of table tennis, especially backhand strokes. This study aims to determine whether there is an effect of individual drill exercises and pair drills on the accuracy of the backhand drive of the table tennis game of Darmaraja High School Sumedang students. The research method used in this study was a quasi-experimental or quasi-experimental research design with the non-equivalent, pretest-posttest design. This research was conducted with two groups that were given treatment. The results of this study were obtained an average increase in the individual drill method group, with a pretest value of 9.4 and a posttest of 10.6. While the results in the pair drill training method group, which was originally 7.9 to 10.08. Data analysis performed on the individual drill group in the two-different test has an average value of sig.0.537 > 0.05, which means that there is no significant difference between the individual and paired drill methods. The results of the study show that both training models can improve the accuracy of Backhand Drive strokes in table tennis games